POWER OF NURSING EDUCATION TO INFLUENCE THE ATTRIBUTES OF STUDENTS IN A PRIVATE COLLEGE OF NURSING - RASHEED , K; ZAFAR , M; FARID , B; RASHEED , B; ARSHAD, H (Biological and Clinical Sciences Research Journal, 2024)
This methodological study addresses a critical gap in the research landscape by exploring the influence of nursing education on the attributes of nursing students in Pakistan. Despite existing studies in countries such as Iran, Egypt, and Finland, satisfactory research on this topic remains elusive. The study aims to develop and validate an instrument tailored for the Pakistani context, specifically focusing on the power of nursing education and its capacity to shape nursing students' attributes. A questionnaire-based approach was employed to gather data, focusing on the extent to which nursing education influences the attributes of student nurses. The analysis of the data revealed encouraging findings regarding the impact of nursing education on various attributes. Notably, improvements were observed in areas such as professional communication, fluidity, and the integration of human values and professional excellence into nursing practice. This study sheds light on the nuanced concept of the power of nursing education from the perspective of nursing professionals. The findings underscore the complexity inherent in this concept, emphasizing its significance within the context of the nursing profession's ethos of compassion, ethics, and care. Importantly, the study highlights the notion of professional influence through nursing education as a valuable concept, vital for fostering the professional growth and development of nursing students. Crucially, the results demonstrate that nursing education plays a pivotal role in enhancing nursing students' professional knowledge and overall development, thereby positively impacting their attributes. By equipping students with the necessary skills and knowledge, nursing education cultivates professionalism and establishes a strong foundation for future nursing practice. This study contributes to the international discourse on nursing education and underscores the importance of tailored research initiatives to understand its impact on nursing students' attributes across diverse cultural and contextual settings.